Combustion performance of jatropha biodiesel in an oil burner system - Arizal, Mohd. Amirul Amin (Penerbit UTM Press, 2015)
Jatropha Curcas is a non-edible plant that can be used for renewable or alternative energy. The seeds of Jatropha contain up to 60 percent oil. The oil can be converted into biodiesel by well-known two-step using acid-base catalytic transesterification. This paper shows the combustion performance of biodiesel derived from Jatropha oil in an oil burner designed for conventional diesel. Biodiesel used in this study is a blend of diesel with Jatropha Methyl Ester (JME) and combustion performance was measured and compared with that of conventional diesel fuel (CDF). The combustion performance of Jatropha biodiesel is based on wall temperature profiles and the amount of gaseous emissions emitted such as nitrous oxide (NOx), sulphur dioxide (SO2) and carbon monoxide (CO). It was demonstrated that biodiesel derived from Jatropha is comparable to the combustion properties of CDF and has high potential to be used as alternative fuel for diesel machines.